Pengaruh Metode Pembelajaran Debat Dan Diskusi Terhadap Prestasi Belajar Ditinjau Dari Kemampuan Berpikir Kritis Mahasiswa - Laxmi Zahara; Sapiruddin Sapiruddin (Universitas Hamzanwadi, 2019)
This research is aimed at finding out 1) the effect of debate and discussion on the students’ learning achievement; 2) the effect of high and low critical thinking ability on the students’ learning achievement; and 3) the interaction between the instructional method and the critical thinking ability on the students’ learning achievement. This research is quantitative administering experiment research. The population is the students of Informatics Education Study Program. The sample is the students who are taking ‘Etika Profesi (Profession Ethics)’ subject in the sixth semester. This grade consists of two classes: 6A and 6B. Based on the research and the data analysis, it is concluded that 1) there is effect on the students’ learning achievement -the students’ learning achievement taught through debating is higher than through discussion; 2) there is effect critical thinking ability on the students’ learning achievement -the students with high critical thinking ability gain higher learning achievement; 3) there is a significant interaction between the instructional method and the students’ critical thinking ability.